2D Transition Metal Dichalcogenide: Unraveling High‐Yield Phase‐Transition Dynamics in Transition Metal Dichalcogenides on Metallic Substrates (Adv. Sci. 7/2019). Issue 7 (3rd April 2019) - Yin, Xinmao; Tang, Chi Sin; Wu, Di; Kong, Weilong; Li, Changjian; Wang, Qixing; Cao, Liang; Yang, Ming; Chang, Yung‐Huang; Qi, Dianyu; Ouyang, Fangping; Pennycook, Stephen J.; et al.
Abstract : In article number 1802093, Wenjing Zhang, Andrivo Rusydi, Andrew T. S. Wee, and co‐workers derive the general trends for the high‐yield phase‐transition‐process of two‐dimensional transition metal dichalcogenides (2D‐TMDs) on metals (Au, Ag, Cu). While each 2D‐TMD possesses different intrinsic 1H‐1T' energy barriers, the use of a metallic substrate with higher chemical reactivity plays a more pivotal role in increasing the 1H‐1T' phase‐transition yield which is brought about via the enhancement of the interfacial hybridizations.